IMPLEMENTATION OF THE FAMILY HOPE PROGRAM - Saepudin, Saepudin; Wahyudin, Cecep (Jurnal Ilmu Administrasi Negara, 2024)
The survival of the community in each region is part of government development; with families who are financially vulnerable in meeting their basic needs, the government is obliged to assist in the form of assistance channeled through the Family Hope Program (PKH). This research aims to analyze the implementation of the Family Hope program in the Ciawi District by adopting four main plans: communication, resources, organization, and bureaucratic structure. The author used quantitative research methods, with a descriptive approach where the statement was distributed to 15 people from recipient communities and aid providers as respondents. Based on the research results, it was found that the Family Hope program in the Ciawi sub-district was running well. This can be seen from respondents’ responses to interviews with the Bogor Regency Social Service and the results of distributing questionnaires showing an average dimension value of 4.25. So, based on these findings, the Bogor Regency Social Service maintains good values and continues to implement plans in accordance with the aims and objectives determined by law. And can be used as input to PKH organizers in the Ciawi area. Improving oneself is a form of responsibility to PKH recipients because this will build more trust in the community. In other words, this research impacts the welfare of the people who receive the benefits of the PKH program.